Dose-dependent effects of capsaicin on intestinal morphology and microbiota composition in mice: Structural, immunohistochemical, and microbial insights - Kai Li; Jianghai Xu; Siying Chen; Aifei Du; Shaohua Feng; Shibin Yuan; Bangyuan Wu (Veterinary World)
Background and Aim: Capsaicin (CAP), the pungent component of chili peppers, possesses diverse bioactive properties, including antioxidant, anti-inflammatory, and antimicrobial effects. However, its impact on gastrointestinal integrity and microbial ecology remains dose-dependent and incompletely understood. This study aimed to investigate the effects of varying CAP doses on intestinal morphology, tight junction protein expression, goblet cell density, mucosal injury markers, and gut microbiota composition in mice.